Wave telescope technique for MMS magnetometer. Issue 10 (24th May 2016) - Narita, Y.; Plaschke, F.; Nakamura, R.; Baumjohann, W.; Magnes, W.; Fischer, D.; Vörös, Z.; Torbert, R. B.; Russell, C. T.; Strangeway, R. J.; Leinweber, H. K.; Bromund, K. R.; et al.
Abstract: Multipoint measurements are a powerful method in studying wavefields in space plasmas. The wave telescope technique is tested against magnetic field fluctuations in the terrestrial magnetosheath measured by the four Magnetospheric Multiscale (MMS) spacecraft on a spatial scale of about 20 km. The dispersion relation diagram and the wave vector distribution are determined for the first time in the ion‐kinetic range. Moreover, the dispersion relation diagram is determined in a proxy plasma rest frame by regarding the low‐frequency dispersion relation as a Doppler relation and compensating for the apparent phase velocity. Fluctuations are highly compressible, and the wave vectors have an angle of about 60° from the mean magnetic field. We interpret that the measured fluctuations represent a kinetic‐drift mirror mode in the magnetosheath which is dispersive and in a turbulent state accompanied by a sideband formation. Key Points: First‐time determination of magnetosheath turbulence properties in the ion‐kinetic range First‐time successful application of interferometric method to MMS magnetometer data Discovery of dispersive character of mirror mode in the ion‐kinetic range